Analysis of the water‐filling process for crude oil pipelines with a large drop in height. Issue 6 (12th February 2020) - Liu, Enbin; Guo, Bingyan; Wang, Mingjun; Ma, Xi; Peng, Yong
Abstract: To explore the problem of the slack flow and waterhead having a huge impact on the low point of a pipeline during the water‐filling process of a large‐drop pipeline, the crossing section of the Nujiang China‐Myanmar crude oil pipeline (for which the maximum height difference is 1480 m) is taken as an actual case, and water filling of an oil pipe segment with a large drop is simulated based on an OLGA multiphase flow transient simulation. The maximum velocity, pressure, and corresponding liquid holdup at different low points of the pipeline are studied, and the variations of water flow velocity, pressure, and liquid holdup with time at different low points under different load conditions are obtained. A stress analysis of the pipeline is performed through CAESAR II. The results showed that, when the volume flow rate was 900‐2000 m 3 /h, the probability of slug flow in pipe could be reduced by 57%. Meanwhile, the tube pressure fluctuation and damage to the pipeline and equipment are reduced and pipeline transportation efficiency is improved, thereby providing an effective basis for engineering practice. Abstract : A new calculation method is proposed to solve the problem that the water‐air interface evolves into a waterfall flow pattern and accelerates downward under the action of its own gravity and kinetic energy after the waterhead overturns the high point, which producing a large impact load on the low point of the pipeline.